Persepsi masyarakat terhadap dampak pengembangan homestay di desa pakraman padangtegal, ubud - Krismonita, Ni Kadek Junia; Sari, Ni Putu Ratna; Sulistyawati, Agung Sri (Jurnal Kepariwisataan dan Hospitalitas; Vol 8 No 2 (2024): Vol.8,No.2,2024, 2024)
This research is located in Pakraman village, Padangtegal. In this study using the method of observation, in-depth interviews, distributing questionnaires, and literature study. The sampling technique used is purposive sampling using a Likert scale formula, it is calculated that the respondent's questionnaire used is 100 respondents with 26 statements. The data analysis technique used is descriptive qualitative. From the results of this study, it is known that the community's perception of the impact of homestay development in Pakraman Padangtegal village, Ubud obtained a value of 3.93 with agreed or satisfactory criteria obtained from community assessments based on questionnaires. Homestay development has 3 components in its development, Institutional with the existence of Pokdarwis which regulates the course of tourism activities in Pakraman Padangtegal Village. The implementers who directly run the program are non-governmental groups in Padangtegal village. Products offered as tourist attractions in this village. The product will provide an overview of the house that is used to stay and activities that can be done during the homestay. The impact of Covid-19 has had a major impact on various sectors, especially for business actors in the tourism sector, especially Bali, especially Ubud, which relies heavily on the tourism sector. These impacts also revolve in several sectors of people's lives, both in the socio-cultural, economic and environmental sectors. Since the pandemic that occurred in the international region, the economy of every affected country has experienced a slump.   Keywords: Homestay development, impact, community perception, Padangtegal Village